Dysfunction of the Voltage‐Gated K+ Channel β2 Subunit in a Familial Case of Brugada Syndrome. Issue 6 (June 2016) - Portero, Vincent; Le Scouarnec, Solena; Es‐Salah‐Lamoureux, Zeineb; Burel, Sophie; Gourraud, Jean‐Baptiste; Bonnaud, Stéphanie; Lindenbaum, Pierre; Simonet, Floriane; Violleau, Jade; Baron, Estelle; Moreau, Eléonore; Scott, Carol; et al.
Abstract : Background: The Brugada syndrome is an inherited cardiac arrhythmia associated with high risk of sudden death. Although 20% of patients with Brugada syndrome carry mutations in SCN5A, the molecular mechanisms underlying this condition are still largely unknown. Methods and Results: We combined whole‐exome sequencing and linkage analysis to identify the genetic variant likely causing Brugada syndrome in a pedigree for which SCN5A mutations had been excluded. This approach identified 6 genetic variants cosegregating with the Brugada electrocardiographic pattern within the pedigree. In silico gene prioritization pointed to 1 variant residing in KCNAB2, which encodes the voltage‐gated K + channel β2‐subunit (Kvβ2‐R12Q). Kvβ2 is widely expressed in the human heart and has been shown to interact with the fast transient outward K + channel subunit Kv4.3, increasing its current density. By targeted sequencing of the KCNAB2 gene in 167 unrelated patients with Brugada syndrome, we found 2 additional rare missense variants (L13F and V114I). We then investigated the physiological effects of the 3 KCNAB2 variants by using cellular electrophysiology and biochemistry. Patch‐clamp experiments performed in COS‐7 cells expressing both Kv4.3 and Kvβ2 revealed a significant increase in the current density in presence of the R12Q and L13F Kvβ2 mutants. Although biotinylation assays showed no differences in the expression of Kv4.3, the total and submembrane expression of Kvβ2‐R12Q were significantly increased in comparison with wild‐type Kvβ2. Conclusions: Altogether, our results indicate that Kvβ2 dysfunction can contribute to the Brugada electrocardiographic pattern.